Meningkatkan Motivasi Belajar Siswa pada Materi Pribadi yang Unik sebagai Laki-Laki dan Perempuan yang Sederajat dengan Model Problem Based Learning di Kelas X SMK Negeri 3 Kasihan - Christianus Aditya Kurniawan (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Education in Indonesia faces various complex challenges. Therefore, efforts are continuously being made by the government, educational institutions, and society as a whole to increase access, quality, and relevance of education in order to create a young generation that is skilled, competitive, and ready to face global challenges. In the context of the Merdeka Curriculum, Catholic religious education in Indonesia has a focus on developing students' understanding of religion, moral values, and Catholic spirituality. The independent curriculum emphasizes the profile of Pancasila students. In this classroom action research, researchers focused on the dimensions of independence based on the importance of building strong character and mental attitude in the younger generation, especially in facing complex global challenges. The students who are accepted to attend school at SMK Negeri 3 Kasihan are students who are accepted in majors that are not in accordance with their initial interests. Students with this kind of condition tend to feel unmotivated to learn. Based on the above problem conditions, teachers can provide learning experiences by designing learning processes. One learning model that can be applied is Problem Based Learning (PBL) or problem-based learning.